Do cash or digital payment modalities affect community health worker performance? – a case study of a remote refugee settlement in Western Uganda - Michael T Wagaba; David Musoke; Charles Opio; Arthur Bagonza; Juliet Aweko; Hajarah Nakitende; Alex Mulyowa; Michael Ediau; Peter Waiswa; Elizabeth Ekirapa-Kiracho (Global Health Action)
Background There is inadequate evidence about the influence of digital and cash payment modalities on the performance of Community Health Workers (CHWs) in underserved communities, such as refugee settlements. Objective To compare the performance of CHWs when paid in cash or digitally in Kyaka II refugee settlement, Uganda. Methods A comparative cross-sectional mixed methods design was used. Secondary data comprising 247 CHW reports during a six-month period of cash and digital payments were analyzed using Stata v14. Eleven focus group discussions, four in-depth interviews, and ten key informant interviews were conducted among the settlement stakeholders to explore perceptions of the payment methods. Qualitative data were analyzed thematically using Atlas.ti v9. Results CHWs performed better when paid cash than digital payments (t = 5.28; df = 246; p < 0.001). During the cash payment period, at least secondary education (APR 1.71 CI: 1.14–2.58) and having a side occupation (APR 1.58; CI: 1.13–2.21) were positively associated with performance. For digital payments, being male (APR 0.58; CI: 0.34–0.98), serving longer than 9 years (APR 0.87; CI: 0.82–0.93), and being allocated more than 60 households per month (APR 0.31; CI: 0.19–0.52) were negatively associated with CHW performance. Qualitative data revealed that most stakeholders preferred cash due to inconsistent and delayed digital payments. Conclusion CHWs preferred and performed better with cash payments because digital payments were associated with delays and payment shortfalls that demotivated them. Implementers should invest towards averting digital payment shortfalls in remote settings to enhance CHW motivation and performance.